2020
DOI: 10.5430/ijhe.v9n5p259
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Entrepreneurial Attitudes and Constraints: Do the Constraints Predict University Agriculture Graduates’ Attitudes towards Entrepreneurship?

Abstract: This quantitative study analyzed and predicted gender differences of agriculture graduates’ attitudes towards and challenges in entrepreneurship in Botswana. The study adopted a descriptive and correlational survey research design. A valid and reliable questionnaire was used for data collection through a survey of randomly sampled 149 final year agriculture graduate students (n=149). Inferential statistical tools of Independent t-test and Regression analysis were used for data analysis. The findings of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…They found that finance is one of the reasons for gender disparity in entrepreneurship ownership and management within Africa. Furthermore, a similar result was found in Botswana by Baliyan et al (2020). Finance was found as one of the major factors leading to gender inequality in ownership structure of entrepreneurship activities.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…They found that finance is one of the reasons for gender disparity in entrepreneurship ownership and management within Africa. Furthermore, a similar result was found in Botswana by Baliyan et al (2020). Finance was found as one of the major factors leading to gender inequality in ownership structure of entrepreneurship activities.…”
Section: Resultssupporting
confidence: 74%
“…The findings of the mixed method technique further suggested the need to develop new policies that will further ease female accessibility to finance to reduce the imbalances in gender ownership structure and management of entrepreneurship activities in the country. Similar conclusions were drawn from the study by Baliyan, Mosia and Baliya (2020) in Botswana where finance was found as one of the major attitudinal factors responsible for gender inequality in ownership structure and management of entrepreneurship activities. Mahadea and Khumalo (2020) observed storage and infrastructural challenges as some of the factors inhibiting the progress and sustainability of entrepreneurship activities in South Africa.…”
Section: Sustainable Entrepreneurship Ownership and Management Of Smes In South Africasupporting
confidence: 85%
“…Research showed that there was no gender difference at the barriers of entrepreneurship, indicating men and women graduates encounter the same obstacles on entrepreneurship (Baliyan et al, 2020). We also cannot detect a moderating effect between gender inequality and other role models (Bastian et al, 2019).…”
Section: Gender Effects Moderate the Entrepreneurial Mindset On Entre...mentioning
confidence: 56%
“…The literature about an entrepreneur's identity with the gender lens is broad. There are researches describing differences in the area of venture creation and opportunity exploitation (Baliyan et al, 2020;Duygu Seckin & Tutku Seckin, 2019;Lewis et al, 2016;Rambe & Ndofirepi, 2017), motives of venture creation and involvement (Kharlamova & Stavytskyy, 2020;Mungai & Ogot, 2012;Orser et al, 2012), entrepreneurship competence and entrepreneurial intentions (Daliman et al, 2019), or even fear of failure or danger in the venture establishing (Bullough & Renko, 2017;Daoud et al, 2020). Researchers have been looking for conclusions taking into consideration particular grounds for entrepreneurship, e.g.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%